2020
DOI: 10.1109/tbcas.2020.3034444
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Non Anesthetic Preclinical Study Available Extra-Cranial Brain Activator (ECBA) System for the Future Minimally Invasive Human Neuro Modulation

Abstract: In recent years, electroceuticals have been spotlighted as an emerging treatment for various severe chronic brain diseases, owing to their intrinsic advantage of electrical interaction with the brain, which is the most electrically active organ. However, the majority of research has verified only the short-term efficacy through acute studies in laboratory tests owing to the lack of a reliable miniaturized platform for long-term animal studies. The construction of a sufficient integrated system for such a platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In recent years, owing to research that combines classic convoluted neural networks with self-attention approaches (Blanzieri 2021 ; Mahmood 2020 ; Yang et al 2021 ), the performance of networks has greatly increased, resulting in considerable gains. The conventional U-shaped skip connection that was used for medical image categorization has reportedly been superseded by the fusion addition attention gates skip connection, as stated in the research that has been published (Patel et al 2021 ; Lee 2020 ; Pu 2022 ). Despite this, CNN is still the news channel that attracts the most viewers.…”
Section: Review Of Existing Multiorgan Disease Detection Techniquesmentioning
confidence: 99%
“…In recent years, owing to research that combines classic convoluted neural networks with self-attention approaches (Blanzieri 2021 ; Mahmood 2020 ; Yang et al 2021 ), the performance of networks has greatly increased, resulting in considerable gains. The conventional U-shaped skip connection that was used for medical image categorization has reportedly been superseded by the fusion addition attention gates skip connection, as stated in the research that has been published (Patel et al 2021 ; Lee 2020 ; Pu 2022 ). Despite this, CNN is still the news channel that attracts the most viewers.…”
Section: Review Of Existing Multiorgan Disease Detection Techniquesmentioning
confidence: 99%
“…Lee et al successfully developed an implantable device to activate brain neurons. It consists of three parts, a small module of extracranial brain activator, a base station for transmitting power wirelessly, and an intelligent device for monitoring and controlling operations [70]. A small module of a coin size was implanted under the brain's scalp, the base station transfers the power wirelessly to the implanted device to stimulate neurons, and the intelligent device monitors and controls all operations.…”
Section: Neural Stimulations and Electrode Arraysmentioning
confidence: 99%
“…The pre-and post-stimulation studies revealed noticeable brain activity after injecting stimulative signals. Further, this suggests that brain activity causes a significant improvement in memory and sensory skills [70]. Alivisatos et al have focused on the operational effectiveness of brain implants for obsessive-compulsive disorder epilepsy and Parkinson's disease [71].…”
Section: Neural Stimulations and Electrode Arraysmentioning
confidence: 99%